Hole Detection for Quantifying Connectivity in Wireless Sensor Networks: A Survey - Pearl Antil; Amita Malik (Journal of Computer Networks and Communications)
Owing to random deployment, environmental factors, dynamic topology, and external attacks, emergence of holes in wireless sensor networks is inescapable. Hole is an area in sensor network around which sensors cease to sense or communicate due to drainage of battery or any fault, either temporary or permanent. Holes impair sensing and communication functions of network; thus their identification is a major concern. This paper discusses different types of holes and significance of hole detection in wireless sensor networks. Coverage hole detection schemes have been classified into three categories based on the type of information used by algorithms, computation model, and network dynamics for better understanding. Then, relative strengths and shortcomings of some of the existing coverage hole detection algorithms are discussed. The paper is concluded by highlighting various future research directions.